1986
DOI: 10.1007/bf01209686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 100-Hz magnetic fields with various waveforms on the development of chick embryos

Abstract: Chick embryos were exposed during their 52 first hours of development to 100-Hz magnetic fields. Sinusoidal, square and pulsed waveforms were used at average field strengths from 0.1 A/m to 80 A/m. After exposure, the embryos were examined for abnormalities and classified by the developmental stages. When bipolar oscillations (oscillating at both sides of the zero-level) were used, the percentage of abnormal embryos was significantly increased above 1 A/m. In exposure to unipolar square waves, no significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…These frequencies are epidemiologically relevant because they are the frequencies of power transmission in North America and Europe, respectively. Cumulative evidence indicates that the wave form, or the complexity, of the magnetic fields may in some cases be more important than specific frequencies or exposure intensities (Juutilainen et al, 1986;Persinger et al, 2001;Ubeda et al, 1983). Given the pervasiveness of anthropogenic 50-and 60-Hz magnetic fields, anomalies in transmission of these frequencies which effectively create higher and lower frequency ''pulses,'' and the interactions of these fields due to the spatial geometries of their household or industrial origins, the emergence of ''complex'' magnetic fields that have biological relevance FIGURE 4 Mean (AE SEM) number of working memory errors per trial during acquisition and reversal blocks for rats exposed prenatally to sham conditions, the frequency-modulated (FM) wave-form, the multiple complex sequence (MCS) wave form, or the theta-burst stimulation (TBS) wave form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These frequencies are epidemiologically relevant because they are the frequencies of power transmission in North America and Europe, respectively. Cumulative evidence indicates that the wave form, or the complexity, of the magnetic fields may in some cases be more important than specific frequencies or exposure intensities (Juutilainen et al, 1986;Persinger et al, 2001;Ubeda et al, 1983). Given the pervasiveness of anthropogenic 50-and 60-Hz magnetic fields, anomalies in transmission of these frequencies which effectively create higher and lower frequency ''pulses,'' and the interactions of these fields due to the spatial geometries of their household or industrial origins, the emergence of ''complex'' magnetic fields that have biological relevance FIGURE 4 Mean (AE SEM) number of working memory errors per trial during acquisition and reversal blocks for rats exposed prenatally to sham conditions, the frequency-modulated (FM) wave-form, the multiple complex sequence (MCS) wave form, or the theta-burst stimulation (TBS) wave form.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies have revealed effects which may be related to the shape of the field, including disturbances in embryonic development (Delgado, Leal, Monteagudo, & Gracia, 1982;Ubeda, Trillo, Chacon, Blanco, & Leal, 1994), skeletal morphology (Huuskonen, Juutilainen, Julkunen, Maki-Paakkanen, & Komulainen, 1998;Huuskonen, Juutilainen, & Komulainen, 1993;Juutilainen, Huuskonen, & Komulainen, 1997), or behaviors (Persinger, 1969;Persinger & Pear, 1972). However, the temporal structure (shape) of the applied magnetic field rather than its intensity, per se, may be a critical factor for the induction of teratogenic effects (Juutilainen, Harri, Saali, & Lahtinen, 1986;Ubeda, Leal, Trillo, Jimenez, & Delgado, 1983). Some researchers may have failed to find significant results because they did not consider the shape of the applied wave form (Juutilainen et al, 1997;Maffeo et al, 1988;Maffeo, Miller, & Carstensen, 1984).…”
mentioning
confidence: 99%
“…In frog eggs, for example, the cleavage furrows align in parallel with the magnetic field vector (Denegre et al, 1998). Embryogenesis is also affected in the chick (Ubada et al, 1985;Jutilainen et al, 1986;Koch et al, 1993), Drosophila (Ho et al, 1992) and the sea urchin (Levin and Ernst, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few measurements of the extremely low-frequ enc y (ELF) ma gnetic fields with frequencies below I kH z in front o f three VDT models have been published (22). ELF ma gneti c fields ha ve been reported to a ffect chick embryogenesis (4,10,11,25). Because que stions ha ve been ra ised about t he effects of VDT expo sure on pr egnant women (see reference 2), it appea red necessar y to study the magnetic field s around several VDT models .…”
mentioning
confidence: 99%
“…Because the rate of change would be of minor importance at EL F in comparison to VLF, and cert ain suggested biological effe cts of ELF ma gnetic fields seem to be independent of the rat e of change (10,11,15), we chose to mea sur e the amplitude (H ) o f th e magnetic field .…”
mentioning
confidence: 99%